NORTHERN SEA ROUTE AS A FACTOR BEHIND THE IMPLEMENTATION OF RUSSIAN ARCTIC LNG-PROJECTS - Tatarenko, Valeriy; Usikova, Oksana; Lyapina, Olga (Revista Inclusiones, 2020)
Developing and improving the sector of liquefied natural gas production is one of the most promising directions for the nearest future of the Russian gas industry. The major resource areas of natural gas are located in the Northern areas of the country (the Yamal Peninsula and other areas of Arctic zone). Therefore, a logistic component of delivering liquefied natural gas to a consumer is a task of a top priority. The use of emerging opportunities of the Northern Sea Route for solving this problem enables to naturally reduce immediacy and delivery hardships. The major purpose of the conducted study was to identify a variety of issues, arising from the implementation of Arctic projects aimed at producing and consuming liquefied natural gas. The research was intended to define the entire complex of urgent solution-required problems and to assess them in economic terms to enhance the competitiveness of this type of Russian product on the global markets. Thus, the paper analyzes the promising projects of producing and consuming liquefied natural gas in the Russian Arctic sector, as well as exploiting associated Northern Sea Route potential.